2009
DOI: 10.1007/s10681-009-9904-9
|View full text |Cite
|
Sign up to set email alerts
|

Diallel cross analysis for maturity and yield-related traits in melon (Cucumis melo L.)

Abstract: A complete diallel cross study of six local populations of Iranian melon (Eyvanaki, Abasali, Tashkandi, Hose-sorkh, Mashhadi and Nahavand) and one foreign cultivar (Ananasi) was carried out. We investigated maturity, average weight per fruit, yield and acceptable yield in the pruning conditions over a period of two planting seasons. The analysis of variance for all of the characteristics indicated highly significant differences among genotypes. Additive gene effects were most important with respect to average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
43
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(67 citation statements)
references
References 15 publications
13
43
4
1
Order By: Relevance
“…In the present study, the estimates are close to those observed by Silva, Nunes, Costa, Aragão and Maia (2011) for Galia melon lines in different environments of northeastern Brazil. They are also within the range of values observed in some studies conducted in other countries (Randhawa & Singh, 1990;Feyzian, Dehghani, Rezai, & Javaran, 2009). It is noteworthy that the coefficient of genotype determination is inherent to population and environmental conditions, as is heritability.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In the present study, the estimates are close to those observed by Silva, Nunes, Costa, Aragão and Maia (2011) for Galia melon lines in different environments of northeastern Brazil. They are also within the range of values observed in some studies conducted in other countries (Randhawa & Singh, 1990;Feyzian, Dehghani, Rezai, & Javaran, 2009). It is noteworthy that the coefficient of genotype determination is inherent to population and environmental conditions, as is heritability.…”
Section: Resultssupporting
confidence: 82%
“…However, the results obtained in this study show that the lines derived by the program exhibit potential for one environment per se, but not for the other. Nevertheless, it is worth noting that the genetic control of various traits related to melon yield and quality is due to the predominance of nonadditive gene effects (Feyzian et al, 2009). Thus, even when there is inconsistent performance in the two environments, it is possible that these lines may be used in the formation of hybrids to be recommended for both Mossoró and Baraúna.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of SCA × Location was only significant for days to opening of the first female flower. Similar results regarding yield were demonstrated in melon (Cucumis melo L.; Feyzian et al, 2009). General and specific combining ability effects over location were recorded (Tables 4 and 5).…”
Section: Resultssupporting
confidence: 80%
“…Diallele cross-designs are frequently used in plant breeding to obtain information and genetic effects for a fixed set of parental lines or to estimate GCA and SCA, which play an important role in control of yield-related components (Virk, 1988). Feyzian et al (2009) emphasized the need to screen parents and crosses before their use in breeding programs and suggested that combining ability analysis based on progeny test data, which is a useful method for evaluating parents and crosses for a wide range of quantitative characters, be used. This investigation was undertaken to determine the mechanism of gene action involved in inheritance of yield components in L. acutangula by combining ability analysis and evaluate effects of sowing date and location on gene expression.…”
mentioning
confidence: 99%
“…Feyzian et al (2009) illustrated that the analysis of variance for all studied characters of melon indicated highly significant differences among genotypes. …”
Section: Results and Discussion Analyses Of Variancesmentioning
confidence: 86%